2018
DOI: 10.1111/jcmm.13533
|View full text |Cite
|
Sign up to set email alerts
|

AmotP130 regulates Rho GTPase and decreases breast cancer cell mobility

Abstract: Angiomotin (Amot) is a newly discovered, multifunctional protein that is involved in cell migration and angiogenesis. However, the role of its isoform, AmotP130, in the regulation of cytoskeleton and metastasis of breast cancer, is unclear. The aim of this study was to investigate the role of AmotP130 in the reorganization of the actin cytoskeleton and the changes of morphology in breast cancer cells through the Rho pathway that influences the invasion and migration of cells. The results suggested that AmotP13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Western blotting assay was done as previously described [33]. Following primary antibodies were used: anti-ANG1 (1:1000, Abcam, UK), anti-PDGFB (1:500, Cell Signaling Technology, UK) and anti-β-actin (1:5000, Proteintech, China).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting assay was done as previously described [33]. Following primary antibodies were used: anti-ANG1 (1:1000, Abcam, UK), anti-PDGFB (1:500, Cell Signaling Technology, UK) and anti-β-actin (1:5000, Proteintech, China).…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that Amot-p80 and Amot-p130 have different functions in breast carcinogenesis. In a previous work from our group, we have shown that Amot-p130 decreases the motility of BCa cells 22 . Here, we have investigated the link between the inhibition of metastasis and Amot-p130 in BCa.…”
Section: Introductionmentioning
confidence: 65%
“…[ 110 ] AMOTp130 can also modulate the Rho signaling pathway to regulate cell cytoskeletal remodeling, inhibiting breast cancer cell invasion. [ 111 ] Moreover, in NF2 ‐null mesothelioma cells, Motins are stabilized, and knockdown of Motins significantly induces YAP/TAZ activity, cell proliferation, and tumorigenesis. [ 24 ] These findings strongly support the tumor suppressor role of Motins.…”
Section: Motins In Tumorigenesismentioning
confidence: 99%